p38δ MAPK: Emerging Roles of a Neglected Isoform - Carol O’Callaghan; Liam J. Fanning; Orla P. Barry (International Journal of Cell Biology)
p38δ mitogen activated protein kinase (MAPK) is a unique stress responsive protein kinase. While the p38 MAPK family as a whole has been implicated in a wide variety of biological processes, a specific role for p38δ MAPK in cellular signalling and its contribution to both physiological and pathological conditions are presently lacking. Recent emerging evidence, however, provides some insights into specific p38δ MAPK signalling. Importantly, these studies have helped to highlight functional similarities as well as differences between p38δ MAPK and the other members of the p38 MAPK family of kinases. In this review we discuss the current understanding of the molecular mechanisms underlying p38δ MAPK activity. We outline a role for p38δ MAPK in important cellular processes such as differentiation and apoptosis as well as pathological conditions such as neurodegenerative disorders, diabetes, and inflammatory disease. Interestingly, disparate roles for p38δ MAPK in tumour development have also recently been reported. Thus, we consider evidence which characterises p38δ MAPK as both a tumour promoter and a tumour suppressor. In summary, while our knowledge of p38δ MAPK has progressed somewhat since its identification in 1997, our understanding of this particular isoform in many cellular processes still strikingly lags behind that of its counterparts.